2011
DOI: 10.1021/nl201441b
|View full text |Cite
|
Sign up to set email alerts
|

Do Two-Dimensional “Noble Gas Atoms” Produce Molecular Honeycombs at a Metal Surface?

Abstract: Anthraquinone self-assembles on Cu(111) into a giant honeycomb network with exactly three molecules on each side. Here we propose that the exceptional degree of order achieved in this system can be explained as a consequence of the confinement of substrate electrons in the pores, with the pore size tailored so that the confined electrons can adopt a noble-gas-like two-dimensional quasi-atom configuration with two filled shells. Formation of identical pores in a related adsorption system (at different overall p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(51 citation statements)
references
References 50 publications
1
50
0
Order By: Relevance
“…44 This size lattice is comparable to the size of defect-free regions in the experimental system. 45 In particular, the steps on this surface have a spacing on this order. This size also allows easy visual inspection without undue finite-size effects, as well as affording reasonable computational costs.…”
Section: Monte Carlo Resultsmentioning
confidence: 98%
“…44 This size lattice is comparable to the size of defect-free regions in the experimental system. 45 In particular, the steps on this surface have a spacing on this order. This size also allows easy visual inspection without undue finite-size effects, as well as affording reasonable computational costs.…”
Section: Monte Carlo Resultsmentioning
confidence: 98%
“…A greater problem was that subsequent experiments showed that pentaquinone (PQ) forms the same ordered structure (albeit less robustly) [36]. See Fig.…”
Section: Honeycomb Netsmentioning
confidence: 99%
“…This renders suspect any explanation in terms of indirect interactions (based on the same Cu surface state). Hence, we proposed an alternative explanation: the structure was stabilized by electrons confined within the honeycomb cell [36]. We made the simplifying assumption that the barriers between cells were infinitely high, so that intercell coupling could be ignored in this zeroth approximation.…”
Section: Honeycomb Netsmentioning
confidence: 99%
See 2 more Smart Citations